Book Review of Assessment Strategies for Online Learning: Engagement and Authenticity, 2018 - Michael Dabrowski (The Canadian Network for Innovation in Education (CNIE), 2020)
Book Review by Michael Dabrowski Assessment strategies for online learning: Engagement and Authenticity, 2018. By Dianne Conrad and Jason Openo, Athabasca University Press 220 pages. doi:10.15215/aupress/9781771992329.01